Social innovation ignored: framing nonprofit activities in European news media - Krlev, Gorgi; Lund, Anker Brink (Voluntas, 2020)
News reporting typically has a dual function: it mirrors what is going on in real life, but it also shapes how actors behave. Previous studies suggest that media presence, by way of shaping public and policy perceptions, influence how well nonprofits are able to raise funds and mobilize human resources. Yet, we are lacking insights into how the third sector is actually framed in the media, in particular with regard to innovation, which increasingly complements the more traditional functions of advocacy and service provision. To find out, we performed a longitudinal content analysis and an in-depth framing analysis on national and regional newspapers from nine European countries. The analyses demonstrate that third sector activities, especially those related to social innovation, are largely ignored. We find no systematic evidence that crises increase news attention to nonprofit activities. The third sector is becoming more newsworthy when it co-engages with government and business actors, but can benefit only little from this “positive glow”. We suggest how research on these matters can be taken forward, with a specific focus on the agenda-setting theory of mass media, the strategic management of nonprofit organizations, and collaboration in the context of social innovation.
Gesehen am 26.10.2020